THE IRREGULARITIES OF TURN-TAKING IN ME BEFORE YOU MOVIE - Purna, Purna; Jaya, Amir; Rohmana, Rohmana (Journal of Teaching of English, 2019)
This research is about the analysis irregularities of turn- taking Â on Â Me Â Before Â You Â movie. Â The Â objectives Â of Â this research were (1) to describe the types irregularities of turn- takings produced by characters in â€œMe Before Youâ€ movie. (2) Â to Â describe Â the Â reasons Â of Â interruption Â turn-takings happened in the movie. This research used a qualitative method to desribe and analyze the utterance. The technique of data collection were (1) watching the movie entitled Me Before You (2) identifying the problems in Me Before You movie (3) formulating the research problems (4) determining the objectives of the study (5) determining theories on context and turn-taking to analyze the data (6) collecting the data manually (7) transferring the chosen data into a data sheet (8) reporting the data. The technique of data analysis were (1) The analysis begun with the searching of the types of irregular turn-takings that are interruption and overlap (2) The reasons why interruption and overlaps emerged in the conversation of the movie are then categorized. The result of this research shows that there is 88.88% of interruption occurred in that movie and 11.11% is about overlapping occurrence.Â Keywords: irregularities, turn- taking, overlapping, interruption